COMPOSITIONAL SEMANTICS OF THE COMPLEX LANGUAGE FACTS WITH THE ENGLISH -ING FORMANT (on the material of Ukrainian) - Viktoria V. Bilousova; Raisa V. Kelembet (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The article focuses on the problems of formal and semantically complex English borrowings analyzed through the prism of cognitive linguistics and with applying its methodological set of approaches. The authors aimed at making an attempt of systematizing the compositional semantics of the complex language facts and determining their derivative character. This intention is realized through the task to identify the mechanism of transferring the word-building meanings to the recipient language where they gain their new meaning and motivation. It is a general fact that compositional semantics of the derivative word in the donor language is built on the evident language facts (base + formant), they possess their own peculiarities of formal and semantic complex and their own motivated character. They determined the choice of the research methods such as comparative, structural, descriptive and typological approaches applying in our work. In this study we try to determine the import of every borrowed word component into its resulted integrative meaning. Cognitive linguistics is directly related with the process of language processing inside our mind and describes the mechanism of its reflecting and producing into the human speech. This is the reason to apply its tools and develop them in aspect of compositional semantics especially in terms of word formation that we use for proving the facts of transporting the word-building meaning that is contained in a formal and semantic borrowed word complex. Inside the recipient language such a complex opens its word-building abilities including their categories in system of words. The borrowed formal and semantic word complex has to be considered from the different sides and not only on the lexical and thematic level or morphemic and grammatical level but also on the word-building one. The borrowed words of this type should be analyzed on the derivative level too, because it is a derivative complex accepted as a part of speech and formant -ing on some stages of assimilation are considered as word-building element. According to the results of research we proved that any language fact is activated in a process of realization its communicative task and then it uses its formal, semantic and creative tools for expressing “new meaning”. The authors’ idea is that the meaning of derivative words (including borrowed words) is derived in a motivated way from the meanings of their components as well as their form and their semantics. It is resulted by the number of formal and semantic similar borrowings that belong to one word-building range. It is motivated by their word components. The speaker understands this type of word because of its special meaning and pronunciation and reflects it in one’s subjective creative language world. This approach for analysis of borrowed language facts let us formulate the following conclusion: creative reflection of the formal and semantic complex of the borrowed words presented as a complex, not a simplex in a speaker’s mind. This complex contains a formant with determined word-building meaning, in our work it is the transliterated English borrowing with -ing formant into Ukrainian.